The effects of vitamin D on all-cause mortality in different diseases: an evidence-map and umbrella review of 116 randomized controlled trials - Cao, Mingyu; He, Chunrong; Gong, Matthew; Wu, Song; He, Jinshen (Frontiers in Nutrition, 2023)
Purpose: To conduct a solid evidence by synthesizing meta-analyses and updated RCTs about the effects of vitamin D on all-cause mortality in different health conditions. Methods: Data Sources: Pubmed, Embase, Web of Science, the Cochrane Library, Google Scholar from inception until 25th April, 2022. Study Selection: English-language, meta-analyses and updated RCTs assessing the relationships between vitamin D and all-cause mortality. Data Synthesis: Information of study characteristics, mortality, supplementation were extracted, estimating with fixed-effects model. A Measurement Tool to Assess Systematic Reviews, Grading of Recommendations Assessment, Development and Evaluation, and funnel plot was used to assess risk of bias. Main Outcomes: All-cause mortality, cancer mortality, cardiovascular disease mortality. Results: 27 meta-analyses and 19 updated RCTs were selected, with a total of 116 RCTs and 149,865 participants. Evidence confirms that vitamin D reduces respiratory cancer mortality (RR, 0.56 [95%CI, 0.33 to 0.96]). All-cause mortality is decreased in patients with COVID-19 (RR, 0.54[95%CI, 0.33 to 0.88]) and liver diseases (RR, 0.64 [95%CI, 0.50 to 0.81]), especially in liver cirrhosis (RR, 0.63 [95%CI, 0.50 to 0.81]). As for other health conditions, such as the general health, chronic kidney disease, critical illness, cardiovascular diseases, musculoskeletal diseases, sepsis, type 2 diabetes, no significant association was found between vitamin D and all-cause mortality. Conclusions: Vitamin D may reduce respiratory cancer mortality in respiratory cancer patients and all-cause mortality in COVID-19 and liver disorders’ patients. No benefits showed in all-cause mortality after vitamin D intervention among other health conditions. The hypothesis of reduced mortality with vitamin D still requires exploration. Registration: CRD42021252921, 3rd June 2021